Layer-by-layer coated nanoliposomes for oral delivery of insulin. Issue 2 (9th December 2020) - Zhang, Yiming; Xiong, Gordon Minru; Ali, Yusuf; Boehm, Bernhard O.; Huang, Ying Ying; Venkatraman, Subbu
Abstract : Nanosulin – a highly stable multilayer insulin-coated nanoliposome, enhanced insulin permeation across the intestinal epithelium and maintained bioactivity via oral administration in vivo . Abstract : Crossing the intestinal epithelial cell barrier safely and reaching the blood with therapeutic levels of bioactive insulin have been the ultimate goal of oral insulin delivery. The optimum way to overcome the barrier lies in the design of an efficient high drug loading carrier, that can protect insulin from the harsh Gastrointestinal (GI) environment and enhance its uptake and transport by epithelial cells. In the present study, we developed a multi-layered insulin loading strategy on an anionic nanoliposome surface based on electrostatic interaction with chitosan. The layer-by-layer (LbL) coated nanoliposomes achieved high insulin loading (10.7% by weight) and offered superior protection with limited release in simulated gastric fluid (SGF) (about 6% in 1 h), simulated intestinal fluid (SIF) (2% in two weeks), and phosphate buffered saline (PBS) (5% in two weeks). Intracellular imaging revealed that the LbL coated liposomes were internalized and intracellularly trafficked towards the basolateral side of the Caco-2 monolayer. Transported insulin demonstrated retention of bioactivity while crossing the epithelial barrier in the glucose uptake study in 3T3 L1-MBX adipocytes. In rat studies, oral administration of the formulation resulted in rapid absorption with a peak in plasma insulin levels 0.5 h post oral gavaging. This technology thus serves as a promising platform for potential oral insulin applications.